The negative impacts of language performance tests on teachers and students : a case study - Mahfouz, Saiid (Beirut University of Balamand - Faculty of Arts and Social Sciences, 2013)
This study aims to investigate the negative impacts of language tests on teachers and students. The sample consisted of grade-4 students and their language teachers in a private English-medium school. Pre-test and post-test structured interviews were conducted with the teachers, whereas pre-test and post-test close-ended questionnaires were filled out by the students. The interview questions were categorized according to the following themes: stress, test validity, the testing process and feedback on mistakes/errors, quizzes and preplanned tests, and test impacts on students from the teachers perspective, whereas the questionnaire items were categorized according to the following preset themes: stress, test validity quizzes and preplanned tests, and learning from mistakes/errors. The qualitative and quantitative analyses of the teachers and students responses respectively revealed that tests do have negative impacts on both. On the one hand, teachers are forced to work around pre-set dates and deadlines and consequently teach to the test. On the other hand, students are rushed to learn the required material while their styles and needs are overlooked. Tests thus create a stressful environment for teachers and students, which in turn affects their performance negatively in the teaching and learning processes. Recommendations revealed that the schools need to adjust and modify their testing system for the benefit of both teachers and students.
: Mémoire
Keywords: Enseignement des langues Evaluation Scolaire; Teaching languages School Evaluation